Enhanced photocatalytic oxidation of free cyanide using hydrogen-treated TiO2: effect of reduction temperature - Mitzy Y Pérez-Patiño; José M Barrera-Andrade; Elizabeth Rojas-García; Lina A Calzada; Jhon Harrison Sierra-Uribe; Ciro Falcony; Miguel A Valenzuela; Elim Albiter (Materials Research Express, 2023)
Hydrogen-treated titanium dioxide (grey TiO _2 ) crystals were synthesized through a temperature-programmed reduction of commercial TiO _2 under an H _2 /Ar mixed gas flow at elevated temperatures ranging from 600 to 800 °C. Analytical techniques, including Raman spectroscopy and x-ray Photoelectron Spectroscopy (XPS), were employed to probe the presence of oxygen vacancies in the grey TiO _2 and to track the variation in Ti ^3+ species concentration as a function of temperature. The reduced samples obtained at different temperatures were used as photocatalysts to oxidize free cyanide ions under UV light illumination. Among these, the photocatalysts reduced at 600 °C demonstrated superior activity, converting 30 ppm of free cyanide to cyanate ions within 120 min. This reaction time represents a significant enhancement in efficiency as compared to untreated TiO _2 , which necessitated over 240 min to accomplish the same conversion. The improved performance of grey TiO _2 is ascribed to its elevated photocurrent and the positive shift in the flat band energy, which together accelerate electron transfer and limit electron–hole recombination rates.